Interval Colorectal Cancers following Guaiac Fecal Occult Blood Testing in the Ontario ColonCancerCheck Program - Lawrence Paszat; Rinku Sutradhar; Jill Tinmouth; Nancy Baxter; Linda Rabeneck (Canadian Journal of Gastroenterology and Hepatology)
Background. This work examines the occurrence of interval colorectal cancers (CRCs) in the Ontario ColonCancerCheck (CCC) program. We define interval CRC as CRC diagnosed within 2 years following normal guaiac fecal occult blood testing (gFOBT). Methods. Persons aged 50–74 who completed a baseline CCC gFOBT kit in 2008 and 2009, without a prior history of CRC, or recent colonoscopy, flexible sigmoidoscopy, or gFOBT, were identified. Rates of CRC following positive and normal results at baseline and subsequent gFOBT screens were computed and overall survival was compared between those following positive and normal results. Results. Interval CRC was diagnosed within 24 months following the baseline screen among 0.16% of normals and following the subsequent screen among 0.18% of normals. Interval cancers comprised 38.70% of CRC following the baseline screen and 50.86% following the subsequent screen. Adjusting for age and sex, the hazard ratio (HR) for death following interval cancer compared to CRC following positive result was 1.65 (1.32, 2.05) following the first screen and 1.71 (1.00, 2.91) following the second screen. Conclusion. Interval CRCs following gFOBT screening comprise a significant proportion of CRC diagnosed within 2 years after gFOBT testing and are associated with a higher risk of death.